Answer:
- -36x^3y^7ab^2
- -2x^2y^2
- y = 2x - 2
- 6x^2 + 2x - 6
Explanation:
1) .....................................
(12y^6ab)(-3yx^3b) =
-36x^3y^7ab^2
2) .....................................
-12x^10y^3/6x^8y =
-2x^(10-8) y^(3-1) =
-2x^2y^2
3) .....................................
Equation of the line with slope of 2 and containing the point (4, 6)
Slope intercept form:
- y = mx + b, where m- slope, b- y-intercept
Considering m = 2, x = 4, y = 6
- 6 = 2*4 + b
- 6 = 8 + b
- b = 6 - 8
- b = -2
The the line is:
4) .....................................
- (2x + 3)(3x - 2)=
- 2x(3x) + 2x(-2) + 3(3x) + 3(-2) =
- 6x^2 - 4x + 6x - 6 =
- 6x^2 + 2x - 6